PENGARUH KINERJA KARYAWAN DAN PELAYANAN PERIJINAN DINAS PENDIDIKAN TERHADAP KEPUASAN LEMBAGA PENDIDIKAN DI KABUPATEN SIDOARJO - Muhammad Mufti Mubarok, Muhammad Mufti Mubarok (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2020)
Abstract Customers in Dispendik (Education Service ) of Sidoarjo on employee’s performance to Operational Permit and Grant Service in Education Service of Sidoarjo, it can be concluded as employee performance of the Sidoarjo Education Service in delivery Operational Permit and Grant Service by the customer perception level able to reached 51.34% of the customer expectation level. Performance of Education Service employees perceived that attribute of the employees in providing equal service to the whole people without impartial the status get highest expectation score than other attribute wholly show these attribute service quality that the most important. Index of customer satisfaction on education service based on value of customer index positioned in category P (Satisfy). Therefore Dispendik is necessary to improving their performance to meeting the customer satisfaction by the expectation.